LAMP-2-deficient human B cells exhibit altered MHC class II presentation of exogenous antigens - Crotzer, Victoria L (Blackwell Science Inc, 2010)
Major histocompatibility complex (MHC) class II molecules present antigenic peptides derived from engulfed exogenous proteins to CD4(+) T cells. Exogenous antigens are processed in mature endosomes and lysosomes where acidic proteases reside and peptide-binding to class II alleles is favoured. Hence, maintenance of the microenvironment within these organelles is probably central to efficient MHC class II-mediated antigen presentation. Lysosome-associated membrane proteins such as LAMP-2 reside in mature endosomes and lysosomes, yet their role in exogenous antigen presentation pathways remains untested. In this study, human B cells lacking LAMP-2 were examined for changes in MHC class II-restricted antigen presentation. MHC class II presentation of exogenous antigen and peptides to CD4(+) T cells was impaired in the LAMP-2-deficient B cells. Peptide-binding to MHC class II on LAMP-2-deficient B cells was reduced at physiological pH compared with wild-type cells. However, peptide-binding and class II-restricted antigen presentation were restored by incubation of LAMP-2-negative B cells at acidic pH, suggesting that efficient loading of exogenous epitopes by MHC class II molecules is dependent upon LAMP-2 expression in B cells. Interestingly, class II presentation of an epitope derived from an endogenous transmembrane protein was detected using LAMP-2-deficient B cells. Consequently, LAMP-2 may control the repertoire of peptides displayed by MHC class II molecules on B cells and influence the balance between endogenous and exogenous antigen presentation.